2009
DOI: 10.2320/matertrans.m2009175
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Toxic Gases on Iron-Incorporated Na-A Zeolites Synthesized from Melting Slag

Abstract: Iron incorporated zeolites were prepared from Na-A type zeolite synthesized from melting slag and FeCl 3 solution and applied as adsorbents for NH 3 and H 2 S gases. Iron incorporated zeolite was pelletized, calcined and used for gas adsorption experiment. XRD analyses of the zeolite revealed that Fe 3þ concentration of solution more than 90 mM could destruct the zeolite network structure. It was observed that the gas adsorption capacities of these zeolite pellets depend significantly on iron concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Lee et al [34] have investigated iron incorporated Na-Y zeolite synthesized from melting slag which includes a sodium silicate solution and sodium aluminate as the key component. In this experiment a packed bed column was used to remove H 2 S. The exit gases were analyzed by using a gas detector and breakthrough concentration was monitored after column.…”
Section: Zeolite Na-y Exchanged By Different Metalsmentioning
confidence: 99%
“…Lee et al [34] have investigated iron incorporated Na-Y zeolite synthesized from melting slag which includes a sodium silicate solution and sodium aluminate as the key component. In this experiment a packed bed column was used to remove H 2 S. The exit gases were analyzed by using a gas detector and breakthrough concentration was monitored after column.…”
Section: Zeolite Na-y Exchanged By Different Metalsmentioning
confidence: 99%
“…Guo et al found that calcination could change a zeolite structure by means such as crystal structure collapse, water removal, phase change, and bond rupture. When the calcination temperature was high, the crystal and surface structure of the zeolite changed significantly and even melted at 800 °C, resulting in a decrease in the active surface area …”
Section: Resultsmentioning
confidence: 99%
“…When the calcination temperature was high, the crystal and surface structure of the zeolite changed significantly and even melted at 800 °C, resulting in a decrease in the active surface area. 32 …”
Section: Resultsmentioning
confidence: 99%
“…There are many types of zeolites with different structure and properties [11,25,48,61,62]. In general, the performance of unmodified zeolites in removing H2S at low temperatures is poor [63][64][65]. Typically, the performance of zeolites can be improved by modifying the method of synthesis, exchanging the cations with other elements, and impregnating other chemicals (e.g.…”
Section: Zeolitesmentioning
confidence: 99%